BMC Nursing - Yuan, Jing.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Nursing is an open access, peer-reviewed journal that considers articles on all aspects of evidence-based nursing care; nursing research methods; nursing service delivery, utilization, and evaluation; nursing administration and human resources. BMC Nursing considers articles on the following aspects of nursing: Evidence-based nursing care: All aspects of evidence-based knowledge to inform and transform nursing practice in all settings. Please note that research on specific conditions/diseases or patient populations will be considered if there is a robust background and discussion on nurses$1 (Binvolvement, implications and recommendations for nurses. Nursing research methods: Topics include, but are not limited to: ethics, subject recruitment/retention, sampling, development and testing of psychometric tools, multi-cultural testing studies, meta-analyses techniques, and protocol development. Service organisations, utilization and collaborative care: Resource usage and reduce service delivery costs while maintaining high-quality care, teamwork among healthcare providers, patients, caregivers, and community resources to ensure effective communication and coordinated care. Nursing and interprofessional education: Curriculum and training design for nursing students and staff, integration of new technology in nursing education, competency-based education approaches, strategies for supporting and measuring the achievement of nursing students and staff. As a BMC Series journal, BMC Nursing does not make editorial decisions based on the perceived interest or potential impact of a study. Manuscripts are considered for publication if they are scientifically valid. For research articles, this includes having a clearly defined and sound research question, appropriate methodology and analysis, and adherence to community-agreed standards relevant to the field. .s
Keywords: Nursing; Nursing services$1 (BAdministration.s; Nursing$1 (BResearch.s; Nursing; Nursing Management; Nursing Research